Characterization of polydimethylsiloxane rubber upon photochemical, thermal, salt-fog ageings and exposure to acid vapours - Delor-Jestin, Florence; Tomer, N. S.; Singh, R. P.; Lacoste, Jacques (E-Polymers, 2006)
The changes in the chemical structure and the physical properties of a filled crosslinked polydimethylsiloxane rubber were monitored as a function of various ageing factors. The variables included photochemical, thermal, salt-fog ageings and exposure to acid vapours. Unaged and aged samples were studied by IR spectroscopy, hardness measurements, Differential Scanning Calorimetry (DSC) and thermogravimetric analysis (TGA) coupled with IR spectroscopy. No significant oxidation was detected after all ageings, except for nitric acid treatment. The presence of aluminium trihydrate was clearly identified as responsible for the observed chemical changes. Then an important vulnerability of this filled silicone rubber towards the cross-linking reactions provoked by usual ageings was also detected. The DSC-thermoporosimetry measurements of the mesh size distribution gave a comparison of cross-linking densities for each ageing. The complementary analysis with TGA-IR allowed us to differenciate the thermal stability of the formulation after various ageings and to acquire new knowledge about thermal decomposition.